Integrated analysis of miRNA and mRNA expression profiles in testes of Landrace and Hezuo boars - Zhang, Bo; Yan, Zunqiang; Gao, Yi; Li, Jiyou; Wang, Zike; Wang, Pengfei; Yang, Qiaoli; Huang, Xiaoyu; Gun, Shuangbao (Frontiers in Veterinary Science, 2022)
Precocious puberty is closely related to testicular development and spermatogenesis, and there is increasing evidence that miRNAs are involved in the regulation of testicular development and spermatogenesis. However, little is known about the regulation of microRNAs (miRNAs) during precocious maturation in Hezuo (HZ) boars. In this study, serum Testosterone (T), Estradiol (E2), Follicle-stimulating hormone (FSH) and Luteinizing hormone (LH) levels were detected in HZ and Landrace (LC) boars in the postnatal period at 30, 90, 120, 180 and 240 days, and the testes of HZ and LC boars at 30 and 120 days were used for histological observation. In addition, we performed small RNA-Seq to identify miRNA at sexual immaturity (30-day-old) and maturity (120-day-old) of HZ boar testis (using LC boar as control) to reveal the key miRNA in regulation of precocious puberty. Hormone assay results showed that high levels of T, E2, FSH and LH may be related to precocious sexual maturity of HZ boars, and that FSH may play an important function before sexual maturity. Histological observation showed that HZ boars developed earlier than LC boars and had reached sexual maturity at 120 days. Small RNA-Seq yielded a total of 359 exist miRNAs, 767 known miRNAs and 322 novel miRNAs in 12 samples; 549, 468, 133 and 247 differentially ex-pressed (DE) miRNAs were identified between Ha vs. Hb, La vs. Lb, Ha vs. La and Hb vs. Lb (|log2 fold change| >1 and p < 0.05). Enrichment analysis showed that target genes of these DE miRNAs were enriched in many gene ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) signaling pathways (such as PI3K-Akt, Hippo and Rap1 signaling pathways) were related to testicular development and spermatogenesis. Further screening, some miRNAs (such as ssc-miR-29b, ssc-miR-199b, ssc-miR-383, ssc-miR-149, ssc-miR-615 and ssc-miR-370) were possibly associated with precocious puberty. These results provide new light on miRNA regulatory mechanisms involved in precocious puberty.